2016
DOI: 10.1128/jvi.01615-16
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Is Released via a Noncanonical Secretory Route

Abstract: We analyzed hepatitis C virus (HCV) morphogenesis using viral genomes encoding a mCherry-tagged E1 glycoprotein. HCV-E1-mCherry polyprotein expression, intracellular localization, and replication kinetics were comparable to those of untagged HCV, and E1-mCherry-tagged viral particles were assembled and released into cell culture supernatants. Expression and localization of structural E1 and nonstructural NS5A followed a temporospatial pattern with a succinct decrease in the number of replication complexes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 80 publications
1
32
1
Order By: Relevance
“…To further corroborate these data, Huh7.5 cells were transfected with the J6-E1-mCherry construct that harbors an mCherry sequence inside the variable region of E1 and thus enables the production of mCherry-labeled viral particles. The functionality of this type of fusion protein and the capacity to form viral particles have been established by Bayer et al (68) and confirmed for the construct/experimental system used in this study (see Fig. S3C to G at the URL mentioned above).…”
Section: Time-and Dose-dependent Inhibition Of the Viral Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…To further corroborate these data, Huh7.5 cells were transfected with the J6-E1-mCherry construct that harbors an mCherry sequence inside the variable region of E1 and thus enables the production of mCherry-labeled viral particles. The functionality of this type of fusion protein and the capacity to form viral particles have been established by Bayer et al (68) and confirmed for the construct/experimental system used in this study (see Fig. S3C to G at the URL mentioned above).…”
Section: Time-and Dose-dependent Inhibition Of the Viral Replicationmentioning
confidence: 99%
“…pFK-Luc-J6 was kindly provided by R. Bartenschlager and has been described previously (44). The J6-E1-mCherry (E1R) construct was generated in a manner similar to that described by Bayer et al (68). The mCherry sequence was amplified with the primers fwd (AAACGTACGC GATGGTGAGCAA) and rev (AAACGTACGCCTTGTACAGCTCGT) with the plasmid pmCherry (Clontech) as a template.…”
Section: Methodsmentioning
confidence: 99%
“…Assembled HCV particles exit the cell as cargoes of the vesicular secretory pathway. The Golgi, Rab11a-positive recycling endosomes, and Rab5a/7a/9a-positive endosomes have each been implicated in HCV secretion (Gastaminza et al, 2008, Coller et al, 2012, Wozniak et al, 2016, Lai et al, 2010, Bayer et al, 2016). Secretion of infectious HCV particles requires that the infected cell express apolipoproteins, such as ApoE and ApoB100 (Fukuhara et al, 2014, Hueging et al, 2014), which are associated with the released infectious HCV particles (Catanese et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Dominant negative mutants of Rab GTPases involved in TGN-endosome trafficking inhibited HCV release but did not have a concomitant effect on the secretion of ApoB or ApoE (28). While some studies favor HCV egress through the Golgi route (31)(32)(33), others suggest a noncanonical secretory pathway (34). Intriguingly, the endocytic and endosomal sorting complex required for transport (ESCRT) machineries have also been implicated in HCV secretion (35,36).…”
mentioning
confidence: 99%
“…Intriguingly, the endocytic and endosomal sorting complex required for transport (ESCRT) machineries have also been implicated in HCV secretion (35,36). The intracellular cholesterol transport inhibitor U18666A promotes the accumulation of HCV particles in autophagosomal and exosomal structures, reflecting the involvement of exosomes in HCV secretion (34,37).…”
mentioning
confidence: 99%